Pilonidal Sinus Disease is Associated with Severe Hidradenitis Suppurativa in a Spanish Cohort - Clara Ureña-Paniego; Marta Gamissans-Cañada; Alejandro Molina-Leyva; Jorge Romaní (Medical Journals Sweden, 2023)
Hidradenitis suppurativa is a chronic inflammatory disorder of the hair follicle with a high level of morbidity. Pilonidal sinus disease is a comorbid disorder and may be the reason for first contact with the healthcare system of patients with hidradenitis suppurativa. The aim of this study was to evaluate the frequency of association of pilonidal sinus disease and hidradenitis suppurativa and to explore whether pilonidal sinus disease defines a different clinical profile for patients with hidradenitis suppurativa. A cross-sectional study in which data regarding past history of pilonidal sinus disease, clinical and sociodemographic information were recorded during the first visit to the Hidradenitis Suppurativa Clinic of 2 tertiary hospitals. A total of 839 patients were included in the study. Of these, 51.7% (434/839) were male and mean age was 37.3 ± 13.6 years. Pilonidal sinus disease was present in 32.6% (269/839) of the patients and was associated with an early debut of hidradenitis suppurativa, a higher Hurley stage, inflammatory phenotype and a greater number of fistulas and perianal involvement. Elapsed time between pilonidal sinus disease and diagnosis of hidradenitis suppurativa was associated with higher disease severity. Pilonidal sinus disease is a frequent comorbidity and risk marker for hidradenitis suppurativa disease severity. Pilonidal sinus disease could be a sentinel event to identify patients who would benefit from close treatment and follow-up.